Исследование мотор-колеса для электромобиля с электродвигателем и редуктором на постоянных магнитах с учетом городского и загородного ездовых циклов - Гребеников, Виктор Владимирович; Прыймак, Максим Васильевич (НТУ "ХПИ", 2018)
Приведены результаты исследования характеристик электродвигателя и редуктора с неодимовыми магнитами для мотор-колеса электромобиля. Для заданных габаритов мотор-колеса с магнитным редуктором (внешний диаметр, осевая длина электродвигателя и редуктора) определена конфигурация и размеры магнитной системы электродвигателя и редуктора, при которой достигается требуемое значение момента в заданном диапазоне частоты вращения с учетом ездовых циклов. Расчет характеристик исследуемого электродвигателя и редуктора выполнен в программном пакете Infolytica MotorSolve и Magnet.

The results of a study of the characteristics of an electric motor and a gear with neodymium magnets for the motor-wheel of an electric vehicle are presented. The study of the traction characteristics of the motor-wheel for an electric vehicle was carried out taking into account the European driving cycle, which describes the movement of the vehicle in the city and in the countryside (engine operation in the minimum speed mode, starting and acceleration to a certain speed, braking from one speed to another). For the given dimensions of the motor-wheel with a magnetic gear (outer diameter, axial length of the electric motor and gear), the configuration and dimensions of the magnetic system of the electric motor and gearbox are determined, at which the required torque value is achieved within a given speed range, taking into account drive cycles. Calculation of the characteristics for the investigated electric motor and gear is made by the software package Infolytica MotorSolve and Magnet.
Study of a motor-wheel for an electric vehicle with an electric motor and a gear with permanent magnets, taking into account urban and countryside driving cycles
Keywords: электромагнитный момент; рабочие характеристики; численное моделирование; европейский ездовой цикл; motor-wheel; electric motor; gear with permanent magnets; electromagnetic torque; performance characteristics; numerical simulation; European driving cycle